Uma contribuição da teoria literária para a análise de conteúdo de imagens publicitárias do fim do século XIX e primeira metade do século XX, contemplando aspectos da natureza brasileira - Costa, Luzia Sigoli Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The factors that contribute to the construction process of the concept of Nature have, in literary and visual works, information that reflects the thinking of society in a given time and space. From the understanding of the genesis and historical trajectory of Information Science, the diversity of documents that this Science seeks to embrace and explore as an object of study can be identified. Within this diversity, the complexity presented by literature as well as by image information and more specifically, posters, for the area of Information and Knowledge Organization and Representation, is perceived. Considering such complexity, this research aims to contribute to the formulation of methodological procedures, in the ambit of content analysis of posters, with an end to the elaboration of document products. Taking as the basis Shiyali Ramamrita Ranganathan´s theory, one of the first theorists in Information Science of the 20th century, a theoretical-conceptual approximation between Essential Categories and the elements that make up the structure of rhetorical discourse and literary narrative categories is explored. This choice was made in the light of the potentiality that literary enunciations engender to contribute to the process of conceptual enlargement of Ranganathan categories. In this approximation, a theoretical-conceptual alignment was established, capable of verifying the possibility of an effective contribution of aspects of Literary Theory to content analysis of posters and of their representation by means of the elaboration of summaries or abstracts, in the ambit of Information Science. Use is made of these enlarged categories for analysis of the content presented in each poster, based on procedures from rhetorical discourse reading and concept identification. In this process, the possibility of considering the denotative, as well as the connotative aspects present ...(Complete abstract, click electronic access below)

Os fatores que colaboram com o processo de construção do conceito de Natureza têm nas obras literárias e imagéticas informações que refletem o pensamento da sociedade, num tempo e espaço determinados. A partir do entendimento da gênese e do percurso histórico da Ciência da Informação, pode-se identificar a diversidade documental que essa Ciência busca abarcar e explorar como objeto de estudo e de intervenção. Dentro dessa diversidade, percebe-se a complexidade apresentada tanto pela literatura como pela informação imagética, mais especificamente, cartazística, para a área disciplinar de Organização e Representação da Informação e do Conhecimento. Considerando essa complexidade, esta pesquisa tem como objetivo contribuir para a formulação de procedimentos metodológicos, no âmbito da análise de conteúdo de cartazes, tendo em vista a geração de produtos documentais. Tomando-se como base a Teoria de Shiyali Ramamrita Ranganathan, um dos primeiros teóricos da Ciência da Informação no século XX, explora-se uma aproximação teórico-conceitual entre as Categorias Essenciais e os elementos que compõem a estrutura do discurso retórico e as categorias da narrativa literária. Essa opção foi feita, diante da potencialidade que os enunciados literários suscitam em contribuir para um processo de ampliação conceitual das categorias ranganathianas. Nessa aproximação, estabeleceu-se um alinhamento teóricoconceitual capaz de verificar a possibilidade de uma efetiva contribuição de aspectos da Teoria Literária para a realização de análise de conteúdo cartazístico e de sua representação por meio da elaboração de sínteses ou resumos, no âmbito da Ciência da Informação. Faz-se uso dessas categorias ampliadas , para análise do conteúdo apresentado em cada cartaz, pautando-se em procedimentos de leitura do discurso retórico e identificação de...
Keywords: Organização da informação; Representação do conhecimento (Teoria da informação); Imagem publicitária - Séc. XIX e XX - Análise de conteúdo; Narrativa visual; Representação da natureza; Information organization; Content analysis; Visual narrative; Publicity image; Poster; Representation of nature